2016
DOI: 10.1111/hsc.12337
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of primary care social work for adults with complex health and social needs: a systematic review

Abstract: The prevalence of complex health and social needs in primary care patients is growing. Furthermore, recent research suggests that the impact of psychosocial distress on the significantly poorer health outcomes in this population may have been underestimated. The potential of social work in primary care settings has been extensively discussed in both health and social work literature and there is evidence that social work interventions in other settings are particularly effective in addressing psychosocial need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 49 publications
(91 reference statements)
1
53
0
6
Order By: Relevance
“…Once a set of candidate themes had been established, the refinement of the themes was necessary. Consistent with expert guidelines [ 19 ] and previous relevant research [ 20 ], this process involved reviewing the collated codes and extracts, looking for internal homogeneity, and considering whether the candidate themes formed a coherent pattern and accurately reflected what was evident in the data set as a whole. Redundant themes were discarded, such as those that did not fit the research question or did not appear to have coherence of meaning.…”
Section: Methodsmentioning
confidence: 99%
“…Once a set of candidate themes had been established, the refinement of the themes was necessary. Consistent with expert guidelines [ 19 ] and previous relevant research [ 20 ], this process involved reviewing the collated codes and extracts, looking for internal homogeneity, and considering whether the candidate themes formed a coherent pattern and accurately reflected what was evident in the data set as a whole. Redundant themes were discarded, such as those that did not fit the research question or did not appear to have coherence of meaning.…”
Section: Methodsmentioning
confidence: 99%
“…Health management is closely related to our daily life. Relevant studies have shown that it has a beneficial effect on clinical care, reduces the needs for clinical chronic psychological services, and helps identify the practices of high‐risk groups (McGregor, Mercer, & Harris, ). The focus of the management approach is to improve the health of the population by improving the organization's service quality (Saaty, ).…”
Section: Case Studymentioning
confidence: 99%
“…(McGregor et al, 2018) Working consistently with an individual is also central to success. Fisher (2015: p.12), for example, has noted that "any support worker interacting with someone facing severe and multiple disadvantage becomes a part of that person's social context even if that interaction was a one-off".…”
Section: "I Got Into My Head For Thirteen Years That No-one Cared" (mentioning
confidence: 99%